Factors Influencing The Income Of Fishermen - Aning Kesuma Putri; Ayu Wulandari (Fakultas Ekonomi, Universitas Bangka Belitung, 2020)
The purpose of this research was to determine the variability of fishermen's incomes by looking at the effect of fishermen's experience, fishermen's education, and fisherman's working hours on income. The population of this research is fishermen in East Belitung Regency with a sample of 181 people and Central Bangka Regency as many as 57 people. The method is carried out through quantitative analysis using path analysis, with primary data in the form of interviews and questionnaires to fishermen. The results showed that the variables of fishermen's experience and working hours had a significant effect on the variability of fishermen's income, as evidenced by the probability of significance at 0,000 (below 0.05) and F-count, t-count is greater than F-table, t-table. While education is not a factor of variability in fishermen's income because the results of the F-count, t-count is smaller than the F-table, t-table. Future research should measure the variability of fishermen's incomes using variables of the level of fish production, the amount of credit or debit, side income, and poverty of fishermen, using Micmac and Mactor method.